2022
DOI: 10.3390/polym14122459
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Anticancer Activity of Sunitinib Malate in Breast Cancer through Lipid Polymer Hybrid Nanoparticles Approach

Abstract: In the current study, lipid-polymer hybrid nanoparticles (LPHNPs) fabricated with lipoid-90H and chitosan, sunitinib malate (SM), an anticancer drug was loaded using lecithin as a stabilizer by employing emulsion solvent evaporation technique. Four formulations (SLPN1–SLPN4) were developed by varying the concentration of chitosan polymer. Based on particle characterization, SLPN4 was optimized with size (439 ± 5.8 nm), PDI (0.269), ZP (+34 ± 5.3 mV), and EE (83.03 ± 4.9%). Further, the optimized formulation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…The developed DSM loaded NSPs (D-NSP1-D-NSP4) were characterized for their particle size, PDI, and ZP and measured in the range of 322–544 nm, 0.259–0.431, and −7.7 to −10.8 mV, respectively. Studies have shown that nanoparticles between 40 and 400 nm in size are suitable for ensuring prolonged drug circulation and higher drug accumulation in tumors with reduced renal clearance [ 33 , 34 ]. The size of NSPs with a β-CD:DPC cross linker (1:1.5) was found to be the smallest (322 ± 5.2 nm) compared with NSPs with DPC cross linker (1:6); these results are in agreement with previously reported work [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The developed DSM loaded NSPs (D-NSP1-D-NSP4) were characterized for their particle size, PDI, and ZP and measured in the range of 322–544 nm, 0.259–0.431, and −7.7 to −10.8 mV, respectively. Studies have shown that nanoparticles between 40 and 400 nm in size are suitable for ensuring prolonged drug circulation and higher drug accumulation in tumors with reduced renal clearance [ 33 , 34 ]. The size of NSPs with a β-CD:DPC cross linker (1:1.5) was found to be the smallest (322 ± 5.2 nm) compared with NSPs with DPC cross linker (1:6); these results are in agreement with previously reported work [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using the BIOVIA discovery studio client 4.1, the structure of a polymer unit was constructed, processed, and subjected to the docking process [ 39 ] following the protocol as discussed by Sangpheak W. et al [ 40 ]. Griseofulvin and Resveratrol were selected as a reference since they have been previously shown to have strong binding and applicability in β-cyclodextrin nanosponge drug delivery systems [ 34 , 35 ]. After molecular docking, the docked inclusion complexes with the best ranked CDOCKER energy and hydrogen bond (H-bond) formation between compounds and β-cyclodextrin were then chosen for detailed interpretation and correlation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An in vitro study found SLPN4 released 84.11% of its drug within 48 h, following the Korsemeyer–Peppas model with the Fickian mechanism. It also exhibited potent cytotoxicity against MCF-7 in the BC . Thus, this finding concludes that the SM-loaded LPHNPs could be a promising therapy option in the management of BC cells expressing IGF-1R, which activate intermittently through multiple pathways, causing neoplasm cell proliferation, apoptosis, survival, and resistance to chemotherapeutic agents.…”
Section: Therapeutic Interventions Involving Nanocarriers For Managem...mentioning
confidence: 99%
“…The selected cell line was cultured in a medium composed of Dulbecco's modified Eagle's medium (DMEM) encompassing 10% fetal bovine serum (FBS), and antibiotics (1% penicillin/streptomycin) added to prevent bacterial contamination from both gram-positive and gram-negative bacteria. Glutamine (2mM), and insulin (0.01 mg/ml) were added to support and facilitate the cell growth that required a large amount of proteins and nucleic acids [57], [58].…”
Section: Anti-proliferative Activitymentioning
confidence: 99%